Augustine on Loving Too Much - Stróżyński, Mateusz (Mnemosyne, 2020)
[The article analyzes the friendship narratives contained in Books Two, Three and Four of Augustine’s Confessions, treating them not as biographical accounts, but as illustrations of Augustine’s philosophical ideas, namely, the fall of the soul and the role played in it by love. All those narratives seem to describe a homoerotic dimension of friendship. It is argued that making such homoerotic friendship, and not heterosexual love between man and woman, an allegory of the fall of the soul enables Augustine to show better the mechanism of the fall, namely, its excessive intensity and the fact that it perverts a naturally good relationship of the soul with the whole of creation.]